Background levels and brain organoid impact of RF field exposure in a healthcare environment - Hernández, José A.; Rosca, Andreea; Suárez, Samuel; Coronel, Raquel; Suarez, Oscar J.; Peran-Ramos, Paula; Marina, Pablo; Rabassa, Luis E.; Mateos, Patricia; Liste, Isabel; López-Alonso, Victoria; Torres-Ruiz, Monica; et al. (Frontiers in Antennas and Propagation, 2024)
This study introduces into the empirical and impact evaluation of radiofrequency electromagnetic fields (RF-EMF) radiation exposure in a healthcare environment, focusing on an indoor microenvironment. It also explores the expression of various genes associated with cellular responses, cell proliferation, senescence and apoptotic cell death. The signals from different wireless communication systems at Hospital Universitario de Canarias (HUC) in the Tenerife, Canary Islands, Spain, were examined in 11 locations. Four measurements campaigns have been performed and experimental electric field values were compared as a long-term exposition. The study focuses on four locations with the highest exposure to communication systems (Down Links), analyzing the evolution of the results. LTE B20 DL), GSM+UMTS 900 (DL) ,GSM 1800 (DL), UMTS 2100 (DL), LTE B7 (DL) ) exhibit relatively higher V/m values. In addition, this work presents biological effects on neural stem cells (NSCs) using 3D brain organoids (BOs) exposed to RF signals in a validated and commercial experimental setting, the Giga Hertz Transverse Electromagnetic (GTEM) cell, that allows for the creation of homogeneous field electromagnetic fields in a small, enclosed setting. BOs reproduces the cellular composition and the structure of the developing brain. The frequency with highest contribution (2.174 V/m) observed (1840 MHz) in UMTS has been selected for biological effects evaluation. Analyzing the expression of several genes associated with cellular responses, cell proliferation, senescence and apoptotic cell death, we found that exposition of BO at 1840 MHz did not affect mRNA expressions in the brain of genes related to apoptosis or senescence. However, a decrease in the gene expression for cell proliferation and cell activity markers was observed during the differentiation stage of BOs. Finally, the discussion emphasizes the coexistence and evolution of various heterogeneous networks and services throughout the four measurement campaigns and the E-field levels are consistently well below the exposure limits set by internationally standards and guidelines. Consequently, the results obtained and the methodology presented could serve as a framework for establishing the basis of RF-EMF assessment in future heterogeneous 5G developments, particularly in the millimeter wave (mmWave) frequency range, where the forecast is for massive high-node density networks.